Batting head injury in professional cricket: a systematic video analysis of helmet safety characteristics. Issue 10 (16th February 2013) - Ranson, Craig; Peirce, Nicholas; Young, Mark
Abstract : Background: Batters in cricket are continuing to sustain head and facial injuries despite wearing protective helmets. Objective: To gain an understanding of the types and mechanisms of head injuries sustained by batters wearing a helmet. Methods: Injury type, location and mechanism were categorised via analysis of 35 videos of National or International cricketers sustaining a head injury while batting. Results: 53% of the injuries occurred following ball impact to either the helmet faceguard and peak, or the faceguard alone. Ten injuries (29%) resulted from the ball penetrating the gap between the helmet peak and faceguard. 29% of the injuries involved the ball contacting the face following penetration of the gap between the helmet peak and faceguard. Fractures, lacerations and contusions were the most common injuries associated with face or faceguard impacts while concussion was more commonly associated with impacts to the side or rear of the helmet shell. Many of the injuries described resulted in prolonged or permanent absence from cricket. Conclusions: Significant head and facial injuries occur in cricket batters despite wearing of helmets. Cricket helmet design and associated National and International Safety Standards should be improved to provide increased protection against head injury related to ball impact to the faceguard and shell of the helmet.